On W. J. Crawford’s Studies of Physical Mediumship - Carlos S. Alvarado (Journal of Scientific Exploration, 2014)
These comments are about the context and reception of W. J. Crawford's physical mediumship work. Interestingly, Crawford did not discuss previously relevant work on the subject, nor the conceptual tradition about mediumistic forces discussed by many authors before he published his studies. The latter included ideas to explain phenomena such as telekinesis and materialization. Many writers were skeptical of Crawford's results, while others argued that some of his findings may have been due to what we now call experimenter effects.